Application of the Traditional Game Congklak to Improve Counting Concept Ability - Dwi Fitrianingsih; Ayu Asmah; Henni Anggraini (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
This research is motivated by group A children at Dharma Wanita Persatuan Putukrejo Kindergarten, Malang Regency, who experience difficulties in the concept of counting, thus requiring concrete activities that can improve their counting abilities. Based on these problems, this study introduces the traditional game of congklak to improve the ability to count number sequences 1-10, count objects by applying one-to-one correspondence, calculate quantities, and distinguish between the concepts of many and few. The research method used is Classroom Action Research (CAR), conducted over two cycles, with each cycle consisting of two meetings. The results of this study show that the pre-cycle results obtained an average of 45.8% (MB - Starting to Develop). In Cycle I, Meeting 1 obtained an average of 48.5% (MB), Cycle I, Meeting 2 obtained an average of 53.8% (BSH - Developing as Expected). Cycle II, Meeting 1 obtained an average of 74.4% (BSH), and Cycle II, Meeting 2 obtained an average of 81.7% (BSB - Very Well Developed). The results of this study can be concluded that the traditional game of congklak can improve the counting abilities of group A children at Dharma Wanita Persatuan Putukrejo Kindergarten, Malang Regency.